Seed Morphology of Allium L. (Amaryllidaceae) from Central Asian Countries and Its Taxonomic Implications - Shukherdorj Baasanmunkh; Jae Kyoung Lee; Ju Eun Jang; Min Su Park; Nikolai Friesen; Sungwook Chung; Hyeok Jae Choi (Plants, 2020)
We studied seed macro- and micro-morphological characteristics of 48 Allium species (51 accessions) belonging to 24 sections and 7 subgenera. Our taxonomic sampling focused on the central Asian regions of Uzbekistan, Kyrgyzstan, and Mongolia. The seed length ranged between 1.74 ± 0.16–4.47 ± 0.43 mm and width ranged between 1.06 ± 0.08–3.44 ± 0.23 mm, showing various shapes. The irregular and elongated polygonal testa cells occurred in all investigated species. Seed testa sculptures showed high variation in their anticlinal walls associated with different shapes: straight to with U-, S- or Omega-type undulations among the species. The moderately flat to convex periclinal walls with various sized verrucae or granules were found in all investigated taxa. Based on our research, we conclude that seed characteristics such as size, shape, and the seed testa features show their significant variability, revealing key characteristics to support taxonomic relationships and major clades recovered in the molecular phylogeny of the genus Allium. Especially, the anticlinal wall characteristics were highly variable and decisive at the both section and species levels. In addition, widely varied shapes and sizes of the seeds were remarkably effective to distinguish Allium species.